Synergistic activity of the new ABL-specific tyrosine kinase inhibitor STI571 and chemotherapeutic drugs on BCR-ABL-positive chronic myelogenous leukemia cells - Topaly, Julian; Zeller, W. Jens; Frühauf, Stefan (Leukemia, 2001)
The ABL-specific tyrosine kinase inhibitor STI571 (formerly CGP57148B) induced cytogenetic remissions in 33% of chronic myelogenous leukemia (CML) patients in a phase I trial (Druker et al 1999). Combination therapy may increase this proportion. We tested whether combinations of STI571 and cytarabine or other chemotherapeutic agents such as hydroxyurea, mafosfamide or etoposide would display synergistic activity in BCR-ABL-positive chronic myelogenous leukemia (CML) cell lines derived from patients in blast crisis. In addition, the toxicity of these combinations on BCR-ABL-negative cells was investigated. A tetrazolium-based MTT assay was used to quantify growth inhibition after 48 h of exposure to cytotoxic agents alone and in simultaneous combination with STI571. The drug interactions were analyzed using the median-effect method of Chou and Talalay. The combination index (CI) was calculated according to the classic isobologram equation. At growth inhibition levels of over 50%, STI571 + cytarabine as well as STI571 + etoposide were significantly synergistic (CI < 1, P < 0.05) in the BCR-ABL-positive cell lines evaluated. At 60% inhibition or higher, a similar synergistic pattern became apparent for STI571 + mafosfamide (P < 0.05), while STI571 + hydroxyurea showed ambiguous, cell line-dependent synergism (BV173), additivity (EM-3) or antagonism (K562) in CML cell lines. Furthermore, the BCR-ABL-negative HL-60, KG1A and normal CD34+ progenitor cells were not affected by 0.8 μM STI571, a concentration which produced more than 50% growth inhibition in all BCR-ABL-positive cells tested, and no potentiation of growth inhibition was observed in these BCR-ABL-negative cells when STI571 was combined with chemotherapeutic agents. Our in vitro data with CML blast crisis cell lines strongly suggest that combinations of STI571 with cytarabine or etoposide be rapidly considered for clinical testing.
Gesehen am 26.01.2022